Peranan Kelompok Tani Dalam Pengembangan Kemandirian Petani di Kabupaten Tana Tidung - Midiansyah Effendi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2012)
Objectives of the study are: (1) to determine the role of farmer groups within the frame of farmer empowerment towards self-reliance, (2) to determine the level of independence of farmers in farming, and (3) designing a model of human resource development to realize the independence of farmers through farmer empowerment in farmer groups. This study conducted in Tana Tidung Regency from July until December 2011 since preparation to report writing. Activities in the study include: preparation, field observations, field research (primary and secondary data collection), tabulation and processing of data, analysis and interpretation, and reporting. The study population was a group of farmers in the Tana Tidung. Study sample is a group of farmers at production centers of rice and secondary food crops. As the unit of analysis (or sampel) is the individual farmer for each farmer groups. The collected data were tabulated and analyzed descriptively qualitative. To determine the role of farmer groups in increasing independence, a Spearman rank correlation test (rs) is applied, while to determine the level of independence of farmers conducted in scoring with provisions or categorized as: high, medium and low. The study results show that: (1) the degree of independence of farmer groups in Tana Tidung classified as moderate, (2) the dominant role of farmer groups is a function of the dynamics of working together, as farmers appreciate the similarities and togetherness, a dynamic working groups for social capital face the next farm independence, amid the challenges of price uncertainty and the environment, (3) effective extension methods applied to existing farmer groups in Tana Tidung are: training and visits extension models and models of field school, and (4) Synergy between government service and the role of farmer groups must be strengthened that include: strengthening the personnel and farmers resource, the creation of a stable food security, availability of adequate agricultural infrastructure, and formation of a strong agribusiness institutions.